Creative problem-solving based on local wisdom of Bengkulu community Repung system to enhance higher order thinking skills in science education - Yetty Trisnayanti; Miterianifa Miterianifa; Ahmad Khoiri; Ivoni Susanti (EDUSAINS, 2025)
Higher order thinking skills (HOTS) among Indonesian students remain a challenge, as learners tend to engage in mechanical learning rather than develop critical, analytical, and creative thinking. The study aims to integrate a creative problem-solving model with the local wisdom of the Bengkulu Repung system to enhance students’ higher order thinking skills. A mixed-methods approach was employed, including a quasi-experimental design, questionnaires, and interviews. The sample consisted of 178 urban and 169 rural students, divided into experimental and control groups. Environmental topics were taught over six instructional sessions (12 hours). The assessment instruments comprised ten open-ended questions measuring analytical, evaluative, and creative dimensions. Data was analyzed using ANOVA and Structural Equation Modeling (SEM) with AMOS software. The ANOVA results revealed significant differences in thinking skills based on gender and school location (p < 0.05). The SEM model demonstrated that analytical skills influence evaluative skills, which in turn contribute to creative skills, with all variable relationships being statistically significant. The model provides both conceptual and practical foundations for developing learning interventions based on higher order thinking skills